'The radicals in these Reform times': Politics, Grand juries, and Ireland's Unbuilt Assize Courthouses, 1800–50. (2015) - Butler, Richard J.
Abstract : It is the aim, in this article, to identify the reasons why certain designs for courthouses in early-nineteenth-century Ireland remained unexecuted, and to do so by analysing surviving drawings and placing them in the political context at this time of Irish local government and of the efforts of Westminster politicians to institute reform. The funding and erection of courthouses were managed by grand juries, an archaic form of local government which gave few rights to smaller taxpayers and was widely perceived as an unaccountable institution associated with the ancien régime . In addition to hosting court sittings, courthouses were used by these grand juries for their private meetings and functions. By exploring the agendas and pretensions of these bodies, and by looking at the fluctuating availability of funding sources that were needed to initiate building work, I will argue through a series of Irish case studies that a renewed focus on elite patronage and its associated politics allows a new insight into courthouse building, which places less emphasis than is often the case on, for example, the role played by the changing legal profession in the architectural development of the courthouse. In nineteenth-century Ireland, courthouses demarcated the visible and tangible presence in the urban landscape of the law and state-sanctioned justice. Laws passed by the Irish parliament and then, after its abolition in 1800, by the Westminster government, were enforced in assize courthouses by travelling judges on established 'circuits', visiting each city or county town twice a year (in the spring and summer). These judges travelled with great splendour through the countryside, and were welcomed by a high sheriff at the county border and escorted with military pageantry, ritual, and procession to their destination.